2020
DOI: 10.1007/s40195-020-01055-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Indirect Transformation of Retained Austenite During Tempering on the Charpy Impact Toughness of a Low-Alloy Cr–Mo–V Steel

Abstract: A modified tempering treatment has been designed in order to avoid the direct transformation of retained austenite (Ar) during tempering of a low-alloy Cr-Mo-V steel. Instead of the direct transformation of Ar into ferrite and M 23 C 6 carbides during conventional tempering at 700 °C, transformation into aggregate of ferrite and cementite has been forced by a pre-tempering at 455 °C before conventional tempering. Experiments have been performed on specimens quenched with cooling rates 1.5, 3 and 12 °C/s, provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, the low-temperature impact energy of this steel is not sensitive to the change in the cooling rate, which is mainly attributed to the softening of the martensite matrix and the appearance of spherical carbides during the tempering process. Jiang et al [17] and Li et al [18] studied the effect of different quenching rates on the microstructure and properties of Cr-Mo-V steel after tempering. Jiang et al believed that the decomposition of martensite-austenite (M-A) constituents and the reduction of effective grain size contribute to improving the low-temperature toughness of the material, while Li et al considered that the lath matrix obtained from the sample with higher quenching rate will cause the dispersion distribution of carbides during tempering, thus increasing the toughness.…”
Section: Introductionmentioning
confidence: 99%
“…However, the low-temperature impact energy of this steel is not sensitive to the change in the cooling rate, which is mainly attributed to the softening of the martensite matrix and the appearance of spherical carbides during the tempering process. Jiang et al [17] and Li et al [18] studied the effect of different quenching rates on the microstructure and properties of Cr-Mo-V steel after tempering. Jiang et al believed that the decomposition of martensite-austenite (M-A) constituents and the reduction of effective grain size contribute to improving the low-temperature toughness of the material, while Li et al considered that the lath matrix obtained from the sample with higher quenching rate will cause the dispersion distribution of carbides during tempering, thus increasing the toughness.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for this phenomenon is the evolution of second phase during tempering heat treatment and service. 6,7 Many research 2,3,[8][9][10][11][12] has been conducted on microstructure, mechanical properties and evolution of precipitates of CrMo/CrMoV steel. Jiang et al [13][14][15] indicated that the decomposition of martensiteaustenite (M-A) constituents and the precipitation of carbides in the 2.25Cr1Mo0.25V steel during the tempering process are the primary reasons for the changes in the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%